TINGKAT KEPATUHAN MAHASISWA ASRAMA KARIMUN PUTRI PANAM - Yeni Erya; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Thesis with the title "Student Compliance Level of Karimun Putri Panam Dormitory". This research was conducted at Jalan Bagau Sakti Gang Kuantan, Panam, Pekanbaru, Riau. This is to find out how the level of compliance of female Karimun dormitory students in complying with the rules in the dormitory and what are the factors that affect the level of compliance of female Karimun dormitory students. The data collection technique used a questionnaire with a total sample size of 60 people. The data analysis technique uses Statistical Product and Service Solution (SPPS), the processed data is presented in tabulated form and then analyzed using descriptive quantitative analysis. The results of the study stated that the overall level of compliance with social manners in the Karimun female dormitory was 100% classified as obedient, based on compliance with the adab visiting the Karimun female dormitory, the respondents who obeyed were 93.3%, while the respondents who were less obedient were 6.6%, Based on the compliance of rights and obligations in the Karimun female hostel, 100% of respondents were classified as obedient, while the overall level of compliance based on licensing compliance of respondents who obeyed was 96.6% of respondents, while those who were less obedient were 3.3% of respondents. The influencing factor was being obedient because of the public's actions amounting to 93.3% of respondents, while those who had no effect were being obedient because they wanted to be praised amounting to 100% of respondents.Keywords: Dormitory Compliance, Compliance Level, Dormitory Residents